A method for preparing a carbonized toughened admixture and its product

Through the combination of wet grinding carbonization technology and materials such as MgCl2, the fineness and gelling performance of yellow phosphorus slag are improved, the problems of carbon dioxide emissions and poor flexural properties of concrete in cement production are solved, and efficient carbonization reaction and concrete performance are achieved. promote.

CN116332559BActive Publication Date: 2025-02-07HUBEI UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310197662.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-03
Publication Date
2025-02-07
Estimated Expiration
2043-03-03

AI Technical Summary

Technical Problem

The existing cement production process releases a large amount of carbon dioxide, and the curing rate of yellow phosphorus slag is low, resulting in poor flexural resistance and toughness of large-scale phosphorus slag concrete.

Method used

Through wet grinding carbonization technology, yellow phosphorus slag is combined with materials such as MgCl2 and basalt fibers. MgCl2 is used as a crystal accelerator to increase the generation of amorphous silicone and calcium carbonate whiskers, and high-purity carbon dioxide and nitrogen are introduced to perform pre-carbonic acid. To improve carbonization efficiency and concrete performance.

Benefits of technology

It improves the fineness of yellow phosphorus slag and the performance of gelled material, enhances the compressive strength and flexural properties of concrete, reduces the amount of cement and carbon dioxide emissions, and promotes environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

A method for preparing a carbonized toughening admixture comprises the following steps: first, taking yellow phosphorus slag and crushing it in a crusher to obtain a crushed material; second, taking 50 to 70 parts by weight of the crushed material in step one, taking 100 to 140 parts by weight of water, taking 9 to 14 parts by weight of MgCl2, adding 0.1 to 0.2% by weight of a water reducer, and then putting it into a ball mill; at the same time, introducing carbon dioxide and nitrogen into the ball mill material in the ball mill, wherein the introduction of nitrogen is beneficial to promoting the two The carbon dioxide is dissolved to improve the carbonization efficiency, and pre-carbonation is performed to finally obtain a wet-ground slurry; in step three, 60 to 80 parts by weight of a film-forming agent, 10 to 20 parts by weight of a coupling agent, and 10 to 20 parts by weight of an auxiliary agent are mixed to prepare a surfactant; in step four, 90 parts by weight of the wet-ground slurry obtained in step two, 1 to 3 parts by weight of a surfactant obtained in step three, and 2 to 4 parts by weight of basalt fiber are mixed to obtain a slurry-like admixture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of building materials, and in particular relates to a preparation method of a carbonized toughening admixture and a product thereof. Background Art

[0002] Gases such as carbon dioxide will increase the temperature of the atmosphere by absorbing long-wave radiation, causing global warming. This effect is called the "greenhouse effect", of which carbon dioxide has the greatest impact on the greenhouse effect. In order to solve this problem, Hesam Ostovari et al. proposed a way to achieve a carbon-neutral cement industry through CO2 mineralization. A considerable amount of carbon dioxide can be stored through the mineralization process, and the performance of alkaline solid materials can be improved, which may replace cement. Today, mineral carbonization has become an effective enhancement technology that is energy-saving and environmentally friendly.

[0003] Portland cement, a key ingredient in concrete, releases a large amount of carbon dioxide (CO2) during its production each year. Cement usage is expected to increase due to rapid infrastructure development, especially in Asia and developing countries. Considering the huge consumption of cement, replacing it with supplementary admixtures is the most feasible and direct solution to reduce the environmental impact of cement production. Substituting cement with admixtures can reduce the waste of yellow phosphorus slag.

[0004] Compared with grinding yellow phosphorus slag and then carbonizing it, wet grinding carbonization reduces the surface energy of particles due to the presence of water, preventing agglomeration and reducing the breaking strength of the crushed particles, which is beneficial to the crushing process. While obtaining small-sized particles, the CaCO3 layer formed on the surface is destroyed, thereby increasing the calcium ion dissolution rate, improving the carbonization efficiency, and accelerating the hydration of composite cement. After the slurry material is prepared, it can be directly used in the production of building materials without drying. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a carbonized toughening admixture in view of the above-mentioned situation. By using yellow phosphorus slag to replace cement, the solidification rate of carbon dioxide by yellow phosphorus slag is increased, and the defects of poor flexural properties and toughness of concrete with a large amount of phosphorus slag are improved.

[0006] In order to achieve the above object, the present invention adopts the following technical scheme:

[0007] A method for preparing a carbonized toughening admixture, the specific steps are as follows:

[0008] Step 1, taking yellow phosphorus slag and placing it in a crusher to crush it to obtain crushed material;

[0009] Step 2: Take 50-70 parts by weight of the crushed material in step 1, take 100-140 parts by weight of water, put them into a ball mill, take 9-14 parts by weight of MgCl2, because Mg in the solution 2+ The presence of MgO in the crystal surface will adsorb a lot of impurity ions, thereby reducing the relative growth rate of each crystal face. On the one hand, the surface of the newly formed aragonite nucleus adsorbs Mg 2+ , inhibiting the thermodynamic transformation of aragonite to calcite; on the other hand, Mg is adsorbed on the surface of tiny calcite nuclei. 2 + , the possibility of growing the crystal nucleus to the critical radius and forming the secondary calcite phase crystal nucleus is greatly reduced, so that the aragonite phase can grow in a relatively stable environment. After adding 0.1-0.2% of the mass percentage of the water reducer, the temperature of the ball mill is controlled to be 60-80°C, and carbon dioxide and nitrogen are introduced into the ball mill material in the ball mill at the same time. The introduction of nitrogen is conducive to promoting the dissolution of carbon dioxide and improving the carbonization efficiency. Pre-carbonation is performed to finally obtain the wet-milled slurry;

[0010] Step 3, mixing 60 to 80 parts by weight of a film-forming agent, 10 to 20 parts by weight of a coupling agent, and 10 to 20 parts by weight of an auxiliary agent to prepare a surfactant;

[0011] Step 4: Take 90 parts by weight of the wet-grinding slurry obtained in step 2, 1 to 3 parts by weight of the surfactant obtained in step 3, and 2 to 4 parts by weight of basalt fiber, and mix them to obtain a slurry admixture.

[0012] Furthermore, the particle size of the crushed material in step one is 2 to 8 mm.

[0013] Furthermore, the purity of the carbon dioxide introduced in step 2 is greater than or equal to 99%.

[0014] Furthermore, the purity of the nitrogen introduced in step 2 is greater than or equal to 99%.

[0015] Furthermore, the time for introducing carbon dioxide in step 2 is 5 to 10 minutes.

[0016] Furthermore, the time for introducing nitrogen in step 2 is 5 to 10 minutes.

[0017] Furthermore, in step three, the film-forming agent is an epoxy resin, the coupling agent is one of KH550, KH560 or KH570, and the auxiliary agent is a cationic auxiliary agent.

[0018] Furthermore, the length of the basalt fiber in step 4 is 3-4 mm and 5-8 mm.

[0019] Furthermore, in step 4, the basalt fibers with a length of 3 to 4 mm account for 45% of the total amount of the fibers.

[0020] The present invention also includes an admixture product prepared according to the above steps.

[0021] Beneficial effects of the present invention:

[0022] The present invention reuses yellow phosphorus slag, takes yellow phosphorus slag and basalt fiber as raw materials, and introduces carbon dioxide while wet-grinding the yellow phosphorus slag. During carbonation, MgCl2 is used as a crystal promoter and phosphoric acid in the phosphorus slag to increase amorphous silica gel and calcium carbonate whiskers in the yellow phosphorus slag, without adding an activator, and storing a certain amount of carbon dioxide. The calcium carbonate formed on the surface of the yellow phosphorus slag is broken by the wet-grinding process, the fineness of the yellow phosphorus slag is increased, the compressive strength of concrete is improved, the dissolution of calcium ions is promoted, and the carbonization reaction efficiency is improved.

[0023] The present invention combines the wet grinding carbonization technology with the generation of calcium carbonate whiskers, and utilizes the mixed addition of two different fibers, calcium carbonate whiskers and basalt, to help control the generation of microcracks and fractures at different stages of cement paste, improve the defects of high-volume phosphorus slag concrete in terms of flexural resistance and poor toughness, and improve the cementitious material performance and toughness of the original yellow phosphorus slag. The present invention can reduce the amount of cement used, reduce carbon dioxide emissions, reduce energy consumption, increase the recycling rate of building materials, and is beneficial to environmental protection. DETAILED DESCRIPTION

[0024] The present invention is described in detail below with specific embodiments.

[0025] Embodiment 1,

[0026] 1) Take the yellow phosphorus slag and crush it in a crusher to 2-8 mm.

[0027] Take 50 parts of phosphorus slag after crushing, take 9 parts of MgCl2 as a crystal promoter, take 100 parts of water according to the water-binder mass ratio, and put 0.1% of the naphthalene-based high-efficiency water reducer into a ball mill with an internal volume of 1 L. At the same time, the ball mill is connected to a pressurized pure carbon dioxide bottle with a purity of 99% and a pressurized pure nitrogen bottle with a purity of 99% through a high-pressure pipe. The temperature of the two and the grinding speed of the ball mill can be adjusted by a controller of the prior art, wherein carbon dioxide and nitrogen are respectively introduced at a pressure of 0.5Mpa, and the introduction time is 10 minutes for pre-carbonation to obtain wet-milled slurry. The wet-milling carbon temperature is controlled at 80°C, the mill speed of the wet-milling carbon is 500r / s, and the wet-milling carbon is obtained.

[0028] 2) Mix 60 parts of epoxy resin film-forming agent, 20 parts of KH550 coupling agent, and 20 parts of cationic auxiliary agent to prepare a surfactant;

[0029] 3) Take the obtained wet-grinded slurry, 1 part of the obtained surfactant, and 2 parts of basalt fiber, and stir them for 2 minutes at a slow speed and 2 minutes at a fast speed to obtain a slurry admixture;

[0030] The lengths of basalt fibers are 3-4 mm and 5-8 mm, of which 3-4 mm fibers account for 45% of all fibers.

[0031] The cement admixture of this embodiment is 135 (Kg / m 3 ), slurry admixture 315 (Kg / m 3 )、Water 150(Kg / m 3 )、Sand 733(Kg / m 3 ), stone 1101(Kg / m 3 ) is used to prepare concrete.

[0032] Under standard curing conditions, the experimental results after curing all meet the national standards. Compared with ordinary concrete samples, in the case of large dosage, the compressive strength of the concrete added with the slurry admixture obtained in this embodiment is basically the same as that of ordinary pure cement concrete, and the flexural performance is also improved. At the same time, at least 23kgCO2 is cured per cubic meter of concrete.

[0033] Embodiment 2 is the same as embodiment 1, except that

[0034] 2) Take 60 parts by mass of the crushed phosphorus slag, take 11 parts by mass of MgCl2 as a crystal promoter, take 100 parts of water according to the water-binder mass ratio, and put 0.1% of the naphthalene-based high-efficiency water reducer into a ball mill with an internal volume of 1 L to 2 L. At the same time, the reactor is connected to a pressurized pure carbon dioxide bottle with a purity of 99% and a pressurized pure nitrogen bottle with a purity of 99% through a high-pressure pipe. The temperature and stirring speed of the two can be adjusted by the controller. Slurry A is passed through carbon dioxide for 5 to 10 minutes for pre-carbonation. The carbon dioxide bottle and the nitrogen bottle are respectively passed through at a pressure of 0.5Mpa for 10 minutes, and wet grinding is used to obtain wet-ground slurry B. The temperature of wet grinding carbon is controlled at 80°C, the mill speed of wet grinding carbon is 500r / s, and wet grinding carbon is obtained.

[0035] The cement admixture of this embodiment is 135 (Kg / m 3 ), slurry admixture 315 (Kg / m 3 )、Water 150(Kg / m 3 )、Sand 733(Kg / m 3 ), stone 1101(Kg / m 3 ) is used to prepare concrete.

[0036] Embodiment 3 is the same as embodiment 1, except that

[0037] 2) Take 50 parts by mass of the crushed phosphorus slag, take 9 parts by mass of MgCl2 as a crystal promoter, take 100 parts of water according to the water-binder mass ratio, and put 0.1% of the naphthalene-based high-efficiency water reducer into a ball mill with an internal volume of 1 L to 2 L. At the same time, the reactor is connected to a pressurized pure carbon dioxide bottle with a purity of 99% and a pressurized pure nitrogen bottle with a purity of 99% through a high-pressure pipe. The temperature and stirring speed of the two can be adjusted by the controller. Slurry A is passed through carbon dioxide for 5 to 10 minutes for pre-carbonation. The carbon dioxide bottle and the nitrogen bottle are respectively passed through at a pressure of 0.5Mpa for 10 minutes, and wet grinding is used to obtain wet-ground slurry B. The temperature of wet grinding carbon is controlled at 80°C, the mill speed of wet grinding carbon is 500r / s, and wet grinding carbon is obtained.

[0038] The cement admixture of this embodiment is 135 (Kg / m 3 ), slurry admixture 315 (Kg / m 3 )、Water 150(Kg / m 3 )、Sand 733(Kg / m 3 ), stone 1101(Kg / m 3 ) is used to prepare concrete.

[0039] Embodiment 4 is the same as embodiment 1, except that

[0040] 2) Take 50 parts by mass of the crushed phosphorus slag, take 9 parts by mass of MgCl2 as a crystal promoter, take 100 parts of water according to the water-binder mass ratio, and put 0.1% of the naphthalene-based high-efficiency water reducer into a ball mill with an internal volume of 1 L to 2 L. At the same time, the reactor is connected to a pressurized pure carbon dioxide bottle with a purity of 99% and a pressurized pure nitrogen bottle with a purity of 99% through a high-pressure pipe. The temperature and stirring speed of the two can be adjusted by the controller. Slurry A is passed through carbon dioxide for 5 to 10 minutes for pre-carbonation. The carbon dioxide bottle and the nitrogen bottle are respectively passed through at a pressure of 0.5Mpa for 10 minutes, and wet grinding is used to obtain wet-ground slurry B. The temperature of wet grinding carbon is controlled at 80°C, the mill speed of wet grinding carbon is 500r / s, and wet grinding carbon is obtained.

[0041] The cement admixture of this embodiment is used to prepare concrete according to the ratio of cement 135 (Kg / m), slurry admixture 315 (Kg / m), water 150 (Kg / m), sand 733 (Kg / m), and stone 1101 (Kg / m).

[0042] The cement admixture of this embodiment is 135 (Kg / m 3 ), slurry admixture 315 (Kg / m 3 )、Water 150(Kg / m 3 )、Sand 733(Kg / m 3 ), stone 1101(Kg / m 3 ) is used to prepare concrete.

[0043] Embodiment 5 is the same as embodiment 1, except that

[0044] 1) Take the yellow phosphorus slag and crush it in a crusher to 2-8 mm.

[0045] Take 50 parts of phosphorus slag after crushing, take 9 parts of MgCl2 as a crystal promoter, take 100 parts of water according to the water-binder mass ratio, and put 0.1% of the naphthalene-based high-efficiency water reducer into a ball mill with an internal volume of 1 L. At the same time, the ball mill is connected to a pressurized pure carbon dioxide bottle with a purity of 99% and a pressurized pure nitrogen bottle with a purity of 99% through a high-pressure pipe. The temperature of the two and the grinding speed of the ball mill can be adjusted by a controller of the prior art, wherein carbon dioxide and nitrogen are respectively introduced at a pressure of 0.5Mpa, and the introduction time is 20 minutes, and pre-carbonation is performed to obtain a wet-milled slurry. The wet-milling carbon temperature is controlled at 80°C, the mill speed of the wet-milling carbon is 500r / s, and the wet-milling carbon is obtained.

[0046] 2) Mix 60 parts of epoxy resin film-forming agent, 20 parts of KH550 coupling agent, and 20 parts of cationic auxiliary agent to prepare a surfactant;

[0047] 3) Take the obtained wet-grinded slurry, 1 part of the obtained surfactant, and 2 parts of basalt fiber, and stir them for 2 minutes at a slow speed and 2 minutes at a fast speed to obtain a slurry admixture;

[0048] The lengths of basalt fibers are 3-4 mm and 5-8 mm, of which 3-4 mm fibers account for 45% of all fibers.

[0049] The cement admixture of this embodiment is 135 (Kg / m 3 ), slurry admixture 315 (Kg / m 3 )、Water 150(Kg / m 3 )、Sand 733(Kg / m 3 ), stone 1101(Kg / m 3 ) is used to prepare concrete.

[0050] Embodiment 6 is the same as embodiment 1, except that

[0051] 4) Take the obtained wet-grinded slurry, 1 part of the obtained surfactant, and 4 parts of basalt fibers, and stir them. The stirring time is 2 minutes of slow stirring and 2 minutes of rapid stirring by the mixer to obtain a slurry-like admixture; the length of the basalt fibers is 3-4 mm and 5-8 mm, of which the length of 3-4 mm accounts for 45% of all the fibers.

[0052] The cement admixture of this embodiment is 135 (Kg / m 3 ), slurry admixture 315 (Kg / m 3 )、Water 150(Kg / m 3 )、Sand 733(Kg / m 3 ), stone 1101(Kg / m 3 ) is used to prepare concrete.

[0053] The solid phase amount of CO2 (or carbonation efficiency) and calcium carbonate (CaCO3) during the carbonation of water were determined by thermogravimetric analysis (TGA). The concrete prepared in each embodiment was molded into 100×100×400mm specimens for flexural strength test according to the "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" and 150×150×150mm cubic specimens for compressive strength test. The test results are shown in the following table:

[0054]

[0055] It can be seen from the above table that the concrete prepared by using alternative cement with different solid-liquid ratios, different rotation speeds, different temperatures and different dosages has little difference in flexural and compressive strength of concrete, which reflects the wide applicability of the present invention, and can meet the requirements of flexural and compressive strength of concrete, while fixing a considerable amount of carbon dioxide. The efficiency of carbonization reaction is improved. The defects of poor flexural performance and toughness of high-dosage phosphorus slag concrete are improved, and the cementitious material performance and toughness of the original yellow phosphorus slag are improved.

Claims

1. A method for preparing a carbonized toughening admixture, characterized in that: The following steps are included: Step 1, taking yellow phosphorus slag and placing it in a crusher to crush it to obtain crushed material; Step 2, take 50-70 parts by weight of the crushed material in step 1, take 100-140 parts by weight of water, take 9-14 parts by weight of MgCl2 as a crystal promoter, add 0.1-0.2% by weight of a water reducer, and then put it into a ball mill, control the temperature of the ball mill to 60-80° C., and at the same time, introduce carbon dioxide and nitrogen into the ball mill material in the ball mill for pre-carbonation to finally obtain a wet-milled slurry, wherein the purity of the carbon dioxide is greater than or equal to 99%, the purity of the nitrogen is greater than or equal to 99%, the introduction pressure of the carbon dioxide is 0.5 MPa, and the introduction pressure of the nitrogen is 0.5 MPa; Step 3, mixing 60 to 80 parts by weight of a film-forming agent, 10 to 20 parts by weight of a coupling agent, and 10 to 20 parts by weight of an auxiliary agent to prepare a surfactant; Step 4: Take 90 parts by weight of the wet-grinding slurry obtained in step 2, 1 to 3 parts by weight of the surfactant obtained in step 3, and 2 to 4 parts by weight of basalt fiber, and mix them to obtain a slurry admixture.

2. The method for preparing a carbonized toughening admixture according to claim 1, characterized in that: The particle size of the crushed material in step 1 is 2 to 8 mm.

3. The method for preparing a carbonized toughening admixture according to claim 1, characterized in that: The time for introducing carbon dioxide in step 2 is 5 to 10 minutes.

4. The method for preparing a carbonized toughening admixture according to claim 1, characterized in that: The time for introducing nitrogen in step 2 is 5 to 10 minutes.

5. The method for preparing a carbonized toughening admixture according to claim 1, characterized in that: In step 3, the film-forming agent is epoxy resin, the coupling agent is one of KH550, KH560 or KH570, and the auxiliary agent is a cationic auxiliary agent.

6. The method for preparing a carbonized toughening admixture according to claim 1, characterized in that: The lengths of the basalt fibers in step 4 are 3-4 mm and 5-8 mm.

7. The method for preparing a carbonized toughening admixture according to claim 1, characterized in that: In step 4, the basalt fibers with a length of 3 to 4 mm account for 45% of the total amount of the fibers.

8. An admixture, characterized in that: A product prepared by the method for preparing a carbonized toughening admixture as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for preparation of fracture-resisting and toughened wet grinding pasty admixtures utilizing waste

    CN107459311A

  • Method for carbon sequestration and emission reduction of wet-ground steel slag of iron and steel plant and application

    CN115069362A